Solve for x
x=\frac{\sqrt{38}}{2}+3\approx 6.082207001
x=-\frac{\sqrt{38}}{2}+3\approx -0.082207001
Graph
Share
Copied to clipboard
2=4x\left(x-6\right)
Variable x cannot be equal to 6 since division by zero is not defined. Multiply both sides of the equation by x-6.
2=4x^{2}-24x
Use the distributive property to multiply 4x by x-6.
4x^{2}-24x=2
Swap sides so that all variable terms are on the left hand side.
4x^{2}-24x-2=0
Subtract 2 from both sides.
x=\frac{-\left(-24\right)±\sqrt{\left(-24\right)^{2}-4\times 4\left(-2\right)}}{2\times 4}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 4 for a, -24 for b, and -2 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-24\right)±\sqrt{576-4\times 4\left(-2\right)}}{2\times 4}
Square -24.
x=\frac{-\left(-24\right)±\sqrt{576-16\left(-2\right)}}{2\times 4}
Multiply -4 times 4.
x=\frac{-\left(-24\right)±\sqrt{576+32}}{2\times 4}
Multiply -16 times -2.
x=\frac{-\left(-24\right)±\sqrt{608}}{2\times 4}
Add 576 to 32.
x=\frac{-\left(-24\right)±4\sqrt{38}}{2\times 4}
Take the square root of 608.
x=\frac{24±4\sqrt{38}}{2\times 4}
The opposite of -24 is 24.
x=\frac{24±4\sqrt{38}}{8}
Multiply 2 times 4.
x=\frac{4\sqrt{38}+24}{8}
Now solve the equation x=\frac{24±4\sqrt{38}}{8} when ± is plus. Add 24 to 4\sqrt{38}.
x=\frac{\sqrt{38}}{2}+3
Divide 24+4\sqrt{38} by 8.
x=\frac{24-4\sqrt{38}}{8}
Now solve the equation x=\frac{24±4\sqrt{38}}{8} when ± is minus. Subtract 4\sqrt{38} from 24.
x=-\frac{\sqrt{38}}{2}+3
Divide 24-4\sqrt{38} by 8.
x=\frac{\sqrt{38}}{2}+3 x=-\frac{\sqrt{38}}{2}+3
The equation is now solved.
2=4x\left(x-6\right)
Variable x cannot be equal to 6 since division by zero is not defined. Multiply both sides of the equation by x-6.
2=4x^{2}-24x
Use the distributive property to multiply 4x by x-6.
4x^{2}-24x=2
Swap sides so that all variable terms are on the left hand side.
\frac{4x^{2}-24x}{4}=\frac{2}{4}
Divide both sides by 4.
x^{2}+\left(-\frac{24}{4}\right)x=\frac{2}{4}
Dividing by 4 undoes the multiplication by 4.
x^{2}-6x=\frac{2}{4}
Divide -24 by 4.
x^{2}-6x=\frac{1}{2}
Reduce the fraction \frac{2}{4} to lowest terms by extracting and canceling out 2.
x^{2}-6x+\left(-3\right)^{2}=\frac{1}{2}+\left(-3\right)^{2}
Divide -6, the coefficient of the x term, by 2 to get -3. Then add the square of -3 to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}-6x+9=\frac{1}{2}+9
Square -3.
x^{2}-6x+9=\frac{19}{2}
Add \frac{1}{2} to 9.
\left(x-3\right)^{2}=\frac{19}{2}
Factor x^{2}-6x+9. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x-3\right)^{2}}=\sqrt{\frac{19}{2}}
Take the square root of both sides of the equation.
x-3=\frac{\sqrt{38}}{2} x-3=-\frac{\sqrt{38}}{2}
Simplify.
x=\frac{\sqrt{38}}{2}+3 x=-\frac{\sqrt{38}}{2}+3
Add 3 to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}